Polymer-based dielectric composite material as well as preparation method and application thereof

By introducing metal organic frame powder into polymer-based dielectric composite materials, adsorbing oxygen and free radicals, preventing the oxidation process, and using the negative expansion coefficient and high modulus characteristics of MOF, the problems of deterioration in dielectric properties and high thermal expansion coefficient of polymer-based dielectric composite materials at high temperatures are solved, and the dielectric performance stability and thermal mechanical properties are improved.

CN119752150APending Publication Date: 2025-04-04SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411686441.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing polymer-based dielectric composites are prone to deterioration in dielectric properties at high temperatures and have a high thermal expansion coefficient, which cannot meet the needs of high-frequency and high-speed signal propagation and components miniaturization at the same time.

Method used

Metal organic frame (MOF) powder is introduced into the polymer resin system, and oxygen and free radicals are adsorbed using the porous structure of MOF and open metal sites to prevent the oxidation process, and the thermal expansion coefficient is reduced and the modulus is increased through the negative expansion coefficient and high modulus of MOF.

Benefits of technology

Effectively suppress the deterioration of the dielectric properties of polymer materials, reduce the thermal expansion coefficient, improve the modulus, and meet the needs of high-frequency and high-speed signal propagation and miniaturization of components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752150A_ABST
    Figure CN119752150A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer-based dielectric composite material as well as a preparation method and application thereof. According to the polymer-based dielectric composite material, metal organic framework powder is dispersed in a polymer resin system. According to the polymer-based dielectric composite material disclosed by the invention, the metal organic framework is introduced, so that the dielectric property degradation of the polymer material can be inhibited under the condition of not influencing a cross-linking reaction, the thermal expansion coefficient of the composite material can be reduced in a relatively wide temperature range, and the thermal mechanical property and the mechanical property are improved; therefore, the problems of dielectric degradation and high thermal expansion coefficient are solved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electronic materials, and in particular to a polymer-based dielectric composite material and a preparation method and application thereof. Background Art

[0002] Aging of polymer-based dielectric composites is a common problem in the electronics industry, especially in situations where materials need to maintain ultra-low dielectric loss. Any degradation of dielectric properties will have a serious impact on the performance of electronic components.

[0003] At present, the general approach to solving such problems is to add antioxidants to the composite system. However, conventional small molecule antioxidants have poor durability and are often lost due to volatilization and migration during material processing and storage. In a free radical crosslinking thermosetting system, antioxidants also consume free radical initiators, resulting in a decrease in crosslinking density and an increase in residual double bonds, making the material more susceptible to oxidation.

[0004] In order to reduce the physical loss of small molecule antioxidants and give full play to their anti-aging effects, the prior art proposes the use of supported antioxidants or macromolecular antioxidants. Among them, supported antioxidants are antioxidants that are loaded on the surface of carriers such as silica, montmorillonite, and graphene by chemical or physical methods. Large molecular weight antioxidants, such as small molecules with anti-aging effects grafted onto polymers, effectively inhibit the volatilization and extraction of antioxidants by limiting the diffusion of small molecule antioxidants.

[0005] Moreover, the existing material stabilization approaches are difficult to simultaneously meet the requirements of specific applications for multiple aspects of materials. A typical example is that 5G and 6G electronic devices involve the transmission of high-frequency and high-speed signals and the miniaturization of components, which put forward extremely high requirements on material performance, including ultra-low dielectric loss and low dielectric constant, high crosslinking density and high glass transition temperature, low thermal expansion coefficient and high modulus, etc. The resin system that has been commercialized and successfully applied is a composite system based on hydrocarbon resin and modified polyphenylene ether. The stability of dielectric properties at high temperatures, however, when such materials are used for a long time at normal working temperature (~100°C), due to thermal oxidative aging, their dielectric properties are significantly deteriorated, that is, the dielectric constant and dielectric loss increase. Adding hindered amine and hindered phenol antioxidants to such systems not only cannot effectively prevent the degradation of dielectric properties, but also interferes with the free radical curing reaction, resulting in a decrease in crosslinking density, an increase in unreacted double bonds, and an easier oxidation reaction, which leads to the degradation of dielectric properties. At the same time, due to the reduction in crosslinking density, the thermal expansion coefficient of the material will increase and the mechanical properties will decrease.

[0006] On the other hand, the traditional method to reduce the thermal expansion coefficient of polymers is to add fillers with low expansion coefficients, such as silica. However, such powders themselves do not have the function of inhibiting material oxidation, and due to their own high dielectric constant, they will lead to an increase in the dielectric constant of the composite material.

[0007] In summary, existing materials and technologies have the following problems:

[0008] a) When polymers work at high temperatures for a long time, their dielectric properties deteriorate due to oxidation, resulting in increased dielectric constant and dielectric loss, increased signal attenuation, and affected signal integrity. This will have a fatal impact on the transmission of high-frequency and high-speed signals and the stability of the equipment.

[0009] b) Ultra-low dielectric loss materials required for high-frequency and high-speed equipment and devices are usually prepared by free radical-induced cross-linking reactions of monomers or prepolymers containing double bonds. Due to the characteristics of their structure, they are particularly susceptible to oxidation attacks, so that they show significant dielectric degradation in the early stages of the aging process. In addition, the thermal expansion coefficient of the resin itself is large and cannot meet the application requirements.

[0010] c) Existing methods for inhibiting polymer aging conflict with the curing reaction of the polymer, resulting in incomplete curing and a large number of functional groups that are susceptible to oxidation, which in turn leads to more serious dielectric degradation.

[0011] d) Existing methods for reducing the coefficient of thermal expansion have no effect on inhibiting dielectric aging.

[0012] Therefore, there is currently no method that can effectively suppress the degradation of the dielectric properties of polymer-based composites at high temperatures while taking into account the short-term thermomechanical properties such as the thermal expansion coefficient and mechanical properties of the polymer. Summary of the invention

[0013] The purpose of the present application is to provide an improved polymer-based dielectric composite material and a preparation method and application thereof.

[0014] In order to achieve the above objectives, this application adopts the following technical solutions:

[0015] One aspect of the present application discloses a polymer-based dielectric composite material, wherein a metal organic framework powder is dispersed in a polymer resin system of the polymer-based dielectric composite material.

[0016] It should be noted that the present application creatively introduces metal organic framework (MOF) powder into the polymer resin system of the polymer-based dielectric composite material, which can not only inhibit the degradation of the dielectric properties of the polymer material without affecting the cross-linking reaction, but also reduce the thermal expansion coefficient of the composite material within a wider temperature range, thereby achieving improvements in the thermomechanical and mechanical properties.

[0017] It should also be noted that the polymer-based dielectric composite material of the present application can simultaneously solve the problems of dielectric degradation and high thermal expansion coefficient. The principle is to utilize the porosity, high specific surface area and a large number of open metal sites of MOF to effectively adsorb oxygen, ozone, peroxyl radicals and other components, hinder the oxidation process, so as to achieve the purpose of inhibiting thermal oxidative aging and inhibiting the degradation of dielectric properties; at the same time, since MOF itself has a negative expansion coefficient and a high modulus, its addition reduces the thermal expansion coefficient of the composite material of the present application, while increasing the modulus.

[0018] In one implementation of the present application, the polymer resin system, based on the weight of solid content, adds 0.5-70 parts of metal organic framework powder to every 5-80 parts of polymer resin.

[0019] It should be noted that the polymer-based dielectric composite material of the present application, as long as the metal organic framework powder is added thereto, can have the effect of inhibiting the degradation of dielectric properties, reducing the thermal expansion coefficient, and improving the modulus to varying degrees; however, in order to ensure that the use requirements are met, the present application preferably adds 0.5-70 parts by weight of metal organic framework powder to every 5-80 parts by weight of polymer resin.

[0020] In one implementation of the present application, the polymer resin system is a thermosetting resin system or a thermoplastic resin system.

[0021] In one implementation of the present application, the thermosetting resin system is a vinyl resin system.

[0022] It should be noted that the vinyl resin system is only a specific resin system used in one implementation of the present application; it can be understood that the technical solution and technical effect of adding MOF in the present application are also applicable to other polymer resin systems that need to maintain long-term dielectric performance stability, including various thermosetting resin systems and thermoplastic resin systems.

[0023] In one implementation of the present application, the polymer-based dielectric composite material includes the following raw materials, calculated by solid weight, 0.5-70 parts of metal organic framework powder, 5-80 parts of vinyl resin, and 0.01-5 parts of initiator.

[0024] It should be noted that for the vinyl resin system, the vinyl resin and the initiator are necessary components, and the present application adds metal organic framework powder on the basis thereof. As for the specific selection of the metal organic framework, the vinyl resin and the initiator, reference can be made to the prior art. In order to ensure the performance of the polymer-based dielectric composite material, the preferred technical solution of the present application clearly defines each component.

[0025] In one implementation of the present application, the metal organic framework powder is selected from at least one of MOF-5, MIL-53(Al), MIL-53(Cr), Zn-MOF-74, HKUST-1, UiO-66, ZIF-1, ZIF-2, ZIF-3, ZIF-4, ZIF-5, ZIF-6, ZIF-7, ZIF-8, ZIF-9, ZIF-10, ZIF-22, ZIF-69, ZIF-90, NAFS-1, MIL-47, CAU-1, MIL-101(Cr), CPO-27-Mg, CPO-27-Mn, CPO-27-Co, CPO-27-Ni, CPO-27-Zn, Mn(HCOO)2, Co(HCOO)2, and Ni(HCOO)2.

[0026] In one implementation of the present application, the vinyl resin is selected from at least one of polybutadiene resin, polyisoprene, styrene-butadiene copolymer, styrene-isoprene copolymer, divinylbenzene-butadiene copolymer, divinylbenzene polymer, divinylbenzene-isoprene copolymer, styrene-butadiene-divinylbenzene copolymer, styrene-isoprene-divinylbenzene copolymer, vinyl polyphenylene ether resin, and maleimide prepolymer.

[0027] In one implementation of the present application, the initiator includes dilauroyl peroxide, dibenzoyl peroxide, isopropyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, tert-pentyl peroxypivalate, tert-butyl peroxypivalate, tert-butyl peroxyisobutyrate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, 1,1-di-tert-butyl peroxy-3,5,5-trimethylcyclohexane, 1,1-di-tert-butyl peroxycyclohexane, 2,2-di(tert-butylperoxy)butane, bis(4-tert-butylcyclohexyl) peroxydicarbonate, hexadecyl peroxydicarbonate, At least one of tetradecyl peroxydicarbonate, di-t-amyl peroxide, diisopropylbenzene peroxide, bis(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di-tert-butylperoxyhexane, 2,5-dimethyl-2,5-di-tert-butylperoxyhexyne, diisopropylbenzene hydroperoxide, isopropylbenzene hydroperoxide, t-amyl hydroperoxide, tert-butyl hydroperoxide, tert-butyl peroxide isopropylbenzene, diisopropylbenzene hydroperoxide, tert-butyl peroxycarbonate-2-ethylhexanoate, tert-butyl peroxycarbonate-2-ethylhexyl ester, n-butyl 4,4-di(tert-butylperoxy)valerate, methyl ethyl ketone peroxide, and cyclohexane peroxide.

[0028] It should be noted that in the resin system of the present application, such as the vinyl resin system, the vinyl resin and the initiator are the resin matrix, and the metal organic framework powder is the filler. On this basis, 5-40 parts of other polymers, 0.01-30 parts of vinyl monomer compounds, 0.01-40 parts of flame retardants, and 0.01-50 parts of inorganic fillers can also be added according to demand. The addition of these components can make the prepared polymer-based dielectric composite material have corresponding properties. Among them, other polymers are selected from at least one of styrene-butadiene diblock copolymer, styrene-butadiene-styrene triblock copolymer, styrene-isoprene diblock copolymer, and styrene-isoprene-styrene triblock copolymer. The vinyl monomer compound is selected from at least one of divinylbenzene, triallyl isocyanurate, triallyl cyanurate, trimethylallyl isocyanurate, trimethylallyl cyanurate, trihydroxyethyl isocyanurate, tert-butylstyrene, diallyl isophthalate, diallyl phthalate, trimethylolpropane triacrylate, and pentaerythritol tetraacrylate. The flame retardant includes a bromine-containing flame retardant and / or a phosphorus-containing flame retardant. The inorganic filler includes at least one of crystalline silica, fused silica, spherical silica, angular silica, hollow silica, glass powder, aluminum nitride, boron nitride, silicon carbide, silicon carbide aluminum, aluminum hydroxide, magnesium hydroxide, titanium dioxide, strontium titanate, barium titanate, zinc oxide, zirconium oxide, aluminum oxide, beryllium oxide, magnesium oxide, barium sulfate, talc, clay, calcium silicate, calcium carbonate, and mica.

[0029] Another aspect of the present application discloses the application of the polymer-based dielectric composite material in electronic components.

[0030] Another aspect of the present application discloses an electronic component using the polymer-based dielectric composite material of the present application.

[0031] It should be noted that the electronic components of the present application, due to the use of the polymer-based dielectric composite materials of the present application, have long-term, stable low dielectric properties, as well as low thermal expansion coefficient and high modulus in a wide temperature range, and can meet the needs of high-frequency and high-speed signal transmission and miniaturization of components in various electronic devices.

[0032] Another aspect of the present application discloses a method for preparing the polymer-based dielectric composite material of the present application, comprising dispersing metal organic framework powder in a solvent to prepare a metal organic framework suspension, dispersing the raw materials of the polymer resin system in a solvent to prepare a resin solution, uniformly mixing the metal organic framework suspension and the resin solution, adding an initiator to react, and then removing the solvent and curing to obtain the polymer-based dielectric composite material of the present application.

[0033] It should be noted that the preparation method of the application can refer to the existing preparation method of polymer-based dielectric composite materials. The difference is that the present application adds metal organic framework powder, that is, the metal organic framework powder is dispersed in a solvent to make a metal organic framework suspension, the metal organic framework suspension and the resin solution are mixed evenly, and then an initiator is added. The remaining steps such as removing the solvent and curing can refer to the prior art and are not specifically limited here. As for the solvent used, the prior art can also be referred to. For example, in one implementation of the present application, toluene is used as the solvent for both the metal organic framework suspension and the resin solution.

[0034] Due to the adoption of the above technical solution, the beneficial effects of this application are:

[0035] The polymer-based dielectric composite material of the present application, by introducing a metal organic framework, can not only inhibit the degradation of the dielectric properties of the polymer material, but also reduce the thermal expansion coefficient of the composite material within a wide temperature range without affecting the cross-linking reaction, thereby achieving improvements in thermomechanical and mechanical properties, thereby simultaneously solving the problems of dielectric degradation and high thermal expansion coefficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a schematic diagram of the preparation process of the polymer-based dielectric composite material in the embodiment of the present application;

[0037] Figure 2 is a SEM surface morphology image of the polymer-based dielectric composite material in the embodiment of the present application;

[0038] Figure 3 is a SEM image of the metal-organic framework material in the embodiment of the present application;

[0039] Figure 4 is a dielectric property-aging time relationship curve of the polymer-based dielectric composite material in the embodiment of the present application;

[0040] Figure 5 is a thermomechanical analysis curve of the polymer-based dielectric composite material in the embodiment of the present application;

[0041] Figure 6 It is a dynamic mechanical analysis curve of the polymer-based dielectric composite material in the embodiment of the present application. DETAILED DESCRIPTION

[0042] The present application has developed a new ultra-low dielectric loss polymer material based on a metal organic framework (MOF) that inhibits dielectric aging and reduces the thermal expansion coefficient, namely the polymer-based dielectric composite material of the present application.

[0043] MOF is a type of porous crystalline material with a 1-D, 2-D or 3-D extended periodic structure, a very large specific surface area and selective adsorption capacity. In addition, many MOFs have other functionalities, such as negative thermal expansion coefficient, high modulus, etc. The present application creatively introduces it into the resin system. Without affecting the cross-linking reaction of the resin system, MOF is used to effectively adsorb oxygen, ozone and peroxy radicals, thereby hindering the oxidation process, thereby inhibiting the oxidation of the material at high temperature and the degradation of the dielectric properties, and improving the reliability of related components in the long-term service process; at the same time, MOF itself has the advantages of negative expansion coefficient and high modulus, and its addition reduces the thermal expansion coefficient of the composite material of the present application and improves the modulus, so that the composite material of the present application can reduce the thermal expansion coefficient of the composite material in a wider temperature range, and achieve improvements in thermomechanical and mechanical properties.

[0044] The present application is further described in detail below through specific examples and drawings. The following examples are only used to further illustrate the present application and should not be construed as limiting the present application.

[0045] The terms used in this application, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. The methods used in the following examples are conventional methods unless otherwise specified, and the raw materials used can be obtained from public commercial channels unless otherwise specified. Unless otherwise specified, all operations are carried out at normal temperature and pressure.

[0046] Example 1

[0047] This embodiment provides an ultra-low dielectric loss thermosetting resin composition with high dielectric stability, that is, a polymer-based dielectric composite material. The raw materials for preparing the thermosetting resin composition include the following components calculated by weight: 40 parts of MOF, 15 parts of polystyrene-butadiene resin, 45 parts of vinyl-terminated polyphenylene ether resin, and 0.3 parts of bis(tert-butylperoxyisopropyl)benzene; 2 grams of MOF is specifically used for the test in this example, and the remaining components are calculated according to the above-mentioned weight ratio. The preparation method of the polymer-based dielectric composite material in this example, such as Figure 1 As shown, the method includes first preparing a MOF suspension and a resin solution separately, then mixing them, adding an initiator for cross-linking, and after the cross-linking is completed, removing the solvent and curing to obtain the polymer-based dielectric composite material of this example. The specific preparation method includes the following steps:

[0048] (1) Weigh each raw material according to its weight.

[0049] (2) MOF was dispersed in 11.5 ml of toluene to prepare a MOF suspension.

[0050] (3) Dissolve polystyrene-butadiene resin and vinyl-terminated polyphenylene ether resin in 57.5 ml of toluene and stir for 4 h to prepare a resin solution.

[0051] (4) Combine the MOF suspension and the resin solution and mix thoroughly.

[0052] (5) Add bis(tert-butylperoxyisopropyl)benzene and mix thoroughly.

[0053] (6) The mixture was poured into a tray with a polytetrafluoroethylene coating and placed in a fume hood for 24 hours to evaporate the solvent; it was then transferred to a vacuum oven at 60°C and 5 mbar to remove the residual solvent.

[0054] (7) Pre-cure in an oven at 153°C for 6 minutes.

[0055] (8) The pre-cured composition is crushed, ground, and sieved to obtain a powder of 80-100 mesh.

[0056] (9) In a hot press, at 210° C. for 90 minutes, the composition was cured into a sample sheet of about 0.5 mm, thereby obtaining the polymer-based dielectric composite material of this example.

[0057] Example 2

[0058] This embodiment provides an ultra-low dielectric loss thermosetting resin composition with high dielectric stability. The raw materials for preparing the thermosetting resin composition include the following components calculated by weight: 20 parts of MOF UiO-66, 20 parts of polystyrene-butadiene resin, 60 parts of terminal vinyl polyphenylene ether resin, and 0.4 parts of bis(tert-butyl peroxide isopropyl)benzene; 2 grams of MOF is specifically used for the test in this example, and the remaining components are calculated according to the above weight ratio. The polymer-based dielectric composite material of this example is prepared according to the steps of Example 1.

[0059] Example 3

[0060] This embodiment provides an ultra-low dielectric loss thermosetting resin composition with high dielectric stability. The raw materials for preparing the thermosetting resin composition include the following components calculated by weight: 20 parts of MOF HKUST-1, 15 parts of polystyrene-butadiene resin, 45 parts of vinyl-terminated polyphenylene ether resin, and 0.3 parts of bis(tert-butylperoxyisopropyl)benzene; 2 grams of MOF is specifically used for the test in this example, and the remaining components are calculated according to the above weight ratio. The polymer-based dielectric composite material of this example is prepared according to the steps of Example 1.

[0061] Example 4

[0062] This embodiment provides an ultra-low dielectric loss thermosetting resin composition with high dielectric stability. The raw materials for preparing the thermosetting resin composition include the following components calculated by weight: 20 parts of MOF-5, 15 parts of polystyrene-butadiene resin, 45 parts of vinyl-terminated polyphenylene ether resin, and 0.3 parts of bis(tert-butylperoxyisopropyl)benzene; 2 grams of MOF is specifically used for the test in this example, and the remaining components are calculated according to the above weight ratio. The polymer-based dielectric composite material of this example is prepared according to the steps of Example 1.

[0063] Example 5

[0064] This embodiment provides an ultra-low dielectric loss thermosetting resin composition with high dielectric stability. The raw materials for preparing the thermosetting resin composition include the following components calculated by weight: 420 parts of MOF-7, 15 parts of polystyrene-butadiene resin, 45 parts of vinyl-terminated polyphenylene ether resin, and 0.3 parts of bis(tert-butylperoxyisopropyl)benzene; 2 grams of MOF is specifically used for the test in this example, and the remaining components are calculated according to the above weight ratio. The polymer-based dielectric composite material of this example is prepared according to the steps of Example 1.

[0065] Comparative Example 1

[0066] This comparative example provides an ultra-low dielectric loss thermosetting resin composition with added silicon dioxide, and the raw materials for preparing the thermosetting resin composition include the following components calculated by weight: 40 parts of silicon dioxide, 15 parts of polystyrene-butadiene resin, 45 parts of vinyl-terminated polyphenylene ether resin, and 0.3 parts of bis(tert-butylperoxyisopropyl)benzene; 2 grams of silicon dioxide is specifically used for the test, and the remaining components are calculated according to the above weight ratio. Silicon dioxide is used instead of MOF, and the polymer-based dielectric composite material of this example is prepared according to the steps of Example 1.

[0067] Comparative Example 2

[0068] This comparative example provides an ultra-low dielectric loss thermosetting resin composition with an antioxidant added, and the raw materials for preparing the thermosetting resin composition include the following components calculated by weight: 0.2 parts of antioxidant N-isopropyl-N-phenyl-p-phenylenediamine, 25 parts of polystyrene-butadiene resin, 75 parts of terminal vinyl polyphenylene ether resin, and 0.5 parts of bis(tert-butylperoxyisopropyl)benzene; this example specifically uses 0.004 grams of antioxidant for testing, and the remaining components are calculated according to the aforementioned weight ratio. The antioxidant is used instead of MOF, and the polymer-based dielectric composite material of this example is prepared according to the steps of Example 1.

[0069] Comparative Example 3

[0070] This comparative example provides an ultra-low dielectric loss thermosetting resin composition with an antioxidant added, and the raw materials for preparing the thermosetting resin composition include the following components calculated by weight: 0.2 parts of antioxidant 2-acrylic acid-2-(1,1-dimethylethyl)-6-[[3-(1,1-dimethylethyl)-2-hydroxy-5-methylphenyl]methyl]-4-tolyl ester, 25 parts of polystyrene-butadiene resin, 75 parts of terminal vinyl polyphenylene ether resin, and 0.5 parts of bis(tert-butylperoxyisopropyl)benzene; this example specifically uses 0.004 grams of antioxidant for testing, and the remaining components are calculated according to the aforementioned weight ratio. The antioxidant is used instead of MOF, and the polymer-based dielectric composite material of this example is prepared according to the steps of Example 1.

[0071] The polymer-based dielectric composite materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were observed by SEM surface morphology. Some of the results are as follows: Figure 2 The SEM surface morphology observation results show that the MOFs in the polymer matrix are evenly distributed and the compatibility between the components is good.

[0072] The surface morphology of several MOFs used in the examples was observed by SEM, and some of the results are as follows: Figure 3 The results show that the morphology and size of different types of MOFs used in the examples are relatively uniform.

[0073] The polymer-based dielectric composite materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to accelerated aging and then tested for changes in dielectric properties. Specifically, the accelerated aging test was carried out in an oven at 150°C. After aging for different periods of time, the samples were taken out and placed in a dryer to cool to room temperature before testing. The dielectric performance test was carried out at 10 GHz according to the SPDR method of IPC-TM-6502.5.5.15. The unaged sample was dried at 110°C, placed in a dryer to cool to room temperature, and then tested. The dielectric aging performance test results of the embodiments and comparative examples are shown in Table 1, and some dielectric performance-aging time relationship curves are shown in Table 1. Figure 4 shown. Figure 4 In the figure, (a) is the dielectric loss, (b) is the dielectric loss growth rate, (c) is the dielectric constant and (d) is the dielectric constant growth rate.

[0074] Table 1 Dielectric aging performance test results of polymer-based dielectric composites

[0075]

[0076] Table 1 and Figure 4 The results show that the addition of different MOFs can significantly improve the dielectric stability of the composition. f The D of the embodiment is increasing continuously and becomes stable after about 7 days.f It first decreases, reaches a minimum within 24 hours, and then starts to increase. f In 14 days, it only increased by 59%, while the Df of the control group increased by 380% and 439% respectively. k Basically insensitive to thermal aging, D k The change is kept within 10%, and the comparative example shows an overall upward trend, while the examples show a slight decrease in the early stage and then tend to stabilize. Traditional antioxidants, such as comparative examples 2 and 3, will delay the cross-linking reaction of the thermosetting system and have a negative impact on the dielectric properties of the resin system: a portion of the vinyl groups do not react during the curing process, making them susceptible to oxidation and conversion into highly polarizable hydroxyl and carboxyl groups, which can lead to serious degradation of dielectric properties. At the same time, because the antioxidant is consumed during the curing process, it cannot provide antioxidant protection in subsequent accelerated aging experiments. In contrast, UiO-66 draws on unique structural characteristics and properties, including high specific surface area and abundant open metal sites, which enhance the adsorption capacity of oxygen and free radicals and effectively quench peroxide free radicals, thereby effectively blocking the oxidation pathway in the early stages of thermal aging. This shows that the incorporation of UiO-66 into the polymer system can greatly alleviate the degradation of Df, and the higher the concentration of UiO-66, the more obvious the effect.

[0077] Thermomechanical analysis and dynamic mechanical analysis were performed on the polymer-based dielectric composites prepared in the examples and comparative examples. Thermomechanical analysis (TMA) of the samples was performed using NETZSCH TMA402F3 Hyperion (Germany). The TMA test samples (10mm×10mm×2.5mm) were prepared using the same sample preparation process. The TMA test curve is as follows: First, the sample was heated to 250°C at a rate of 10°C / min to eliminate the thermal history, and then cooled to 25°C at a rate of 5°C / min. In the second heating cycle, the sample was heated to 300°C at a rate of 10°C / min, and the CTE value was measured. Dynamic mechanical analysis (DMA) was performed using NETZSCH DMA 242E in tensile mode, with a temperature range from room temperature to 300°C, a heating rate of 5K / min, a frequency of 1Hz, and in air. The sample size is approximately 6.8mm×5mm×0.65mm. The glass transition temperature is determined by the peak value of the loss shear modulus tanδ. The test results are shown in Table 1, and some of the thermomechanical analysis curves are shown in Figure 5 As shown in Figure 2, some dynamic mechanical analysis curve results are shown in Figure 2. Figure 6 As shown. Among them, Figure 5 This is a comparison diagram of the coefficient of thermal expansion CTE in different temperature ranges; Figure 6Figure 1 is the dynamic mechanical analysis curve of different vinyl resin samples, where (a) is the curve of loss shear modulus tanδ changing with temperature, and (b) is the curve of storage shear modulus E' changing with temperature.

[0078] Figure 5 The results show that compared with the control example, the addition of MOF can reduce the thermal expansion coefficient of the composite material due to its unique high modulus and negative thermal expansion properties. Figure 6 The results show that the addition of MOF has little effect on the free radical crosslinking reaction of the thermosetting resin matrix, and the Tg does not change much (as shown in Table 1), while the Tg of the sample with the addition of antioxidants is significantly reduced. The modulus of the composite material of the embodiment is significantly enhanced, and the SiO2 added in the comparative example 1 can also significantly improve the modulus; however, combined with the previous test, it can be seen that the addition of SiO2 does not have the function of inhibiting the oxidation of the material and cannot play a role in inhibiting the degradation of dielectric properties.

[0079] The above contents are further detailed descriptions of the present application in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present application is limited to these descriptions. For ordinary technicians in the technical field to which the present application belongs, several simple deductions or substitutions can be made without departing from the concept of the present application.

Claims

1. A polymer-based dielectric composite material, characterized in that: Metal organic framework powder is dispersed in the polymer resin system of the polymer-based dielectric composite material.

2. The polymer-based dielectric composite material according to claim 1, characterized in that: The polymer resin system, based on solid weight, contains 0.5-70 parts of metal organic framework powder for every 5-80 parts of polymer resin.

3. The polymer-based dielectric composite material according to claim 1, characterized in that: The polymer resin system is a thermosetting resin system or a thermoplastic resin system; Preferably, the thermosetting resin system is a vinyl resin system.

4. The polymer-based dielectric composite material according to claim 3, characterized in that: The polymer-based dielectric composite material comprises the following raw materials, calculated by weight of solid content: 0.5-70 parts of metal organic framework powder, 5-80 parts of vinyl resin, and 0.01-5 parts of initiator.

5. The polymer-based dielectric composite material according to claim 4, characterized in that: The metal organic framework powder is selected from at least one of MOF-5, MIL-53 (Al), MIL-53 (Cr), Zn-MOF-74, HKUST-1, UiO-66, ZIF-1, ZIF-2, ZIF-3, ZIF-4, ZIF-5, ZIF-6, ZIF-7, ZIF-8, ZIF-9, ZIF-10, ZIF-22, ZIF-69, ZIF-90, NAFS-1, MIL-47, CAU-1, MIL-101 (Cr), CPO-27-Mg, CPO-27-Mn, CPO-27-Co, CPO-27-Ni, CPO-27-Zn, Mn (HCOO) 2, Co (HCOO) 2, and Ni (HCOO) 2.

6. The polymer-based dielectric composite material according to claim 4, characterized in that: The vinyl resin is selected from at least one of polybutadiene resin, polyisoprene, styrene-butadiene copolymer, styrene-isoprene copolymer, divinylbenzene-butadiene copolymer, divinylbenzene polymer, divinylbenzene-isoprene copolymer, styrene-butadiene-divinylbenzene copolymer, styrene-isoprene-divinylbenzene copolymer, vinyl polyphenylene ether resin, and maleimide prepolymer.

7. The polymer-based dielectric composite material according to claim 4, characterized in that: The initiator includes dilauroyl peroxide, dibenzoyl peroxide, isopropyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, tert-pentyl peroxypivalate, tert-butyl peroxypivalate, tert-butyl peroxyisobutyrate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, 1,1-di-tert-butyl peroxy-3,5,5-trimethylcyclohexane, 1,1-di-tert-butyl peroxycyclohexane, 2,2-di(tert-butylperoxy)butane, bis(4-tert-butylcyclohexyl) peroxydicarbonate, hexadecyl peroxydicarbonate, dicarbonyl peroxide At least one of ester tetradecyl ester, di-tert-amyl peroxide, diisopropylbenzene peroxide, bis(tert-butyl peroxyisopropyl)benzene, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexyne, diisopropylbenzene hydroperoxide, isopropylbenzene hydroperoxide, tert-amyl hydroperoxide, tert-butyl hydroperoxide, tert-butyl peroxide isopropylbenzene, diisopropylbenzene hydroperoxide, tert-butyl peroxycarbonate-2-ethylhexanoate, tert-butyl peroxycarbonate-2-ethylhexanoate, 4,4-di(tert-butyl peroxy) valerate, methyl ethyl ketone peroxide, and cyclohexane peroxide.

8. Use of the polymer-based dielectric composite material according to any one of claims 1 to 7 in electronic components.

9. An electronic component using the polymer-based dielectric composite material according to any one of claims 1 to 7.

10. The method for preparing the polymer-based dielectric composite material according to any one of claims 1 to 7, characterized in that: The method comprises dispersing metal organic framework powder in a solvent to prepare a metal organic framework suspension, dispersing raw materials of a polymer resin system in a solvent to prepare a resin solution, uniformly mixing the metal organic framework suspension and the resin solution, adding an initiator to react, and then removing the solvent and curing to obtain the polymer-based dielectric composite material.

Citation Information

Patent Citations

  • BT resin composite material containing nano MOFs and preparation method thereof

    CN112694750A

  • Ni-MOF / polymer dielectric composite material, preparation method and energy storage material

    CN114316592A

  • Composite material, articles made using same, and method for producing composite material

    WO2024004663A1